2012
DOI: 10.1158/0008-5472.can-11-3552
|View full text |Cite
|
Sign up to set email alerts
|

KRas Induces a Src/PEAK1/ErbB2 Kinase Amplification Loop That Drives Metastatic Growth and Therapy Resistance in Pancreatic Cancer

Abstract: Early biomarkers and effective therapeutic strategies are desperately needed to treat pancreatic ductal adenocarcinoma (PDAC), which has a dismal 5-year patient survival rate. Here, we report that the novel tyrosine kinase PEAK1 is upregulated in human malignancies, including human PDACs and pancreatic intraepithelial neoplasia (PanIN). Oncogenic KRas induced a PEAK1-dependent kinase amplification loop between Src, PEAK1, and ErbB2 to drive PDAC tumor growth and metastasis in vivo. Surprisingly, blockade of Er… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
137
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 37 publications
6
137
1
Order By: Relevance
“…The central role of Src in pancreatic ductal adenocarcinoma metastasis and progression is well documented (39). PEAK1 is also overexpressed in a variety of cancers, including pancreatic ductal adenocarcinoma, in which it associates with an Src-ErbB2 complex to promote cancer progression and metastasis (18). ErbB2-mediated Src activity increases cancer cell migration and invasion (40), and our previous study showed that PEAK1 mediates the formation of an active Src-ErbB2 complex that drives anchorage-independent growth and carcinogenesis (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The central role of Src in pancreatic ductal adenocarcinoma metastasis and progression is well documented (39). PEAK1 is also overexpressed in a variety of cancers, including pancreatic ductal adenocarcinoma, in which it associates with an Src-ErbB2 complex to promote cancer progression and metastasis (18). ErbB2-mediated Src activity increases cancer cell migration and invasion (40), and our previous study showed that PEAK1 mediates the formation of an active Src-ErbB2 complex that drives anchorage-independent growth and carcinogenesis (18).…”
Section: Discussionmentioning
confidence: 99%
“…PEAK1 is also overexpressed in a variety of cancers, including pancreatic ductal adenocarcinoma, in which it associates with an Src-ErbB2 complex to promote cancer progression and metastasis (18). ErbB2-mediated Src activity increases cancer cell migration and invasion (40), and our previous study showed that PEAK1 mediates the formation of an active Src-ErbB2 complex that drives anchorage-independent growth and carcinogenesis (18). PEAK1-Src-ErbB2 function in a feed-forward loop; however, the mechanism through which this kinase complex promotes migration remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Although it remains to be tested, arguments for an involvement of Src in the KRas-mROS-PKD1 signaling cascade are recent findings showing cooperation of Src and oncogenic KRas in driving pancreatic neoplasia, 28 metastatic growth and therapy resistance in pancreatic cancer. 29 PKD1 can activate NF-kB downstream of ROS, 24,25 and during development of PDA, KRas-mROS-PKD1-NF-kB signaling upregulates the expression of EGF-R, its ligands TGFa and EGF as well as their sheddase ADAM17. 5 Overexpression of EGFR and its ligands occurs frequently in the early development process of PDA.…”
mentioning
confidence: 99%